Who would you kill to save the world? - Colebrook, Claire (Provocations (Lincoln, Neb.), 2023)
"Who Would You Kill to Save the World? examines post-apocalyptic cinema and the way it uses images from the past and present to depict what it means to preserve "the world," as well as who is left out of the narrative of rebuilding society"--